Experimental and Theoretical Study of Chemical Equilibria in the Reacting System of the di-Alkyl Carbonate Synthesis - Verevkin, Sergey P.; Emel'Yanenko, Vladimir N.; Kozlova, Svetlana A.; Smirnova, Irina; Arlt, Wolfgang (Industrial & Engineering Chemistry Research, 2011)
The chemical equilibrium of the reactive system (propylene carbonate + butanol = dibutyl carbonate +1,2-propanediol) was studied in the temperature range (303 to 373) K. in the liquid phase using the method of sealed ampules using K(2)CO(3) as heterogeneous catalyst. This reactive system exhibits a strong nonideal behavior of the mixture compounds in the liquid phase. The knowledge of the activity coefficients is required in order to obtain the thermodynamic equilibrium constants K(a). A well established procedure, COSMO-RS, has been used to assess activity coefficients of the reaction participants in the liquid phase. Enthalpies of reactions of the dialkyl carbonate synthesis reaction in the liquid phase were obtained from temperature dependences of the corresponding thermodynamic equilibrium constants. For the sake of comparison, high-level ab initio calculations of the reaction participants have been performed using the GAUSSIAN-03 program package. Absolute electronic energy values of the molecules have been obtained using G3MP2 level. Using these results calculated equilibrium constants and enthalpies of reaction of the dialkyl carbonates synthesis in the liquid phase based on the principles of statistical thermodynamics are found to be in acceptable agreement with the data obtained from the thermochemical measurements.
Keywords: chem equil reacting system dialkyl carbonate prepn COSMO G3MP2